Human bone marrow-derived Mesenchymal stem cells suppress T cell proliferation by inducing cell cycle arrest - Tong, Chih Kong; Sarmadi, Vahid Hosseinpour; Vidyadaran, Sharmili; Saiful Yazan, Latifah; Seow, Heng Fong; Ramasamy, Rajesh (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2008)
Objective: Mesenchymal stem cells (MSC) are common residents of bone marrow and are defined by their higher self-renewal ability and multilineage differentiation. MSC play an important role in supporting haematopoiesis and therefore are implicated in influencing immune responses. In line with this, MSC have been utilised to treat graft-versus-host disease (GVHD) in order to suppress unwanted T cell proliferation. In this study, we investigated the immuno-suppressive effect of bone marrow derived MSC on T cell proliferation at the cell cycle level. Methods: MSC were generated from human bone marrow and confirmed by their immuno-phenotyping. Resting or PHA stimulated allogeneic peripheral blood mononuclear cells (PBMC) were co-cultured in the presence or absence of MSC. T cell proliferation was accessed by trypan-blue exclusion assay at day three. Consequently cell cycle analysis was carried out to determine the mechanism of anti-proliferation. Results: MSC failed to elicit proliferation at resting T cell. However, proliferation of PHA-stimulated T cells was dramatically inhibited in the presence of MSC in a dose dependent manner (p<0.05). Following the inhibitory activity, MSC prevented activated T cells from entering the S phase of cell cycle by arresting them in the G1 phase. Conclusions: Our findings indicate that MSC escape recognition by T cells and inhibit T cell proliferation by cell cycle arrest at G1 phase. This immuno-suppressive effect is most probably mediated by cell-to-cell contact and/or secreted soluble factors.